(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
Arabic poetics, called “al-Arud,” developed the concept of حرف) harf), which is different from the definitions of syllables known to us. The article presents the results of a computer analysis of the structure of the most famous poem by Imru al-Qays, which confirms the regular 14-syllable character of the poem. If we assume that the concept of the syllable was not known to scholars in the first centuries of Islam and to Khalil Ibn Ahmad al Farahidi, this may indicate that Taha Hussein was wrong in his claims that pre-Islamic poetry was altered in the first centuries of Islam. This is a strong argument for it being the original language used by Imru al-Qays many years before the emergence of Islam. This does not mean that the poem has survived in its entirety, but in our opinion what has survived represents the original language used by Imru al-Qays.